Limited value of myeloablative therapy for late multiple myeloma - Alexanian, R.; Dimopoulos, M.; Smith, T.; Delasalle, K.; Barlogie, B.; Champlin, R. (Blood, 1994)
The utility of myeloablative therapy supported by autologous bone marrow (BM) or blood progenitor cells was assessed in 49 patients with multiple myeloma who had received at least 1 year of prior chemotherapy. Outcomes were compared with those of similar patients who did not receive intensive treatment primarily for socioeconomic reasons. Among patients with disease in resistant relapse despite treatment with vincristine-doxorobucin by continuous infusion with pulse dexamethasone (VAD), a 61% response rate was associated with a median remission time of 5 months. After primary resistance for more than 1 year, 6 of 15 patients responded and the overall survival was similar to that of control patients. For patients with melphalan-resistant disease that responded to VAD, the remission time was similar to that of control patients. Current myeloablative treatments supported by autologous BM or blood stem cells were useful to very few patients with multiple myeloma after the first year of chemotherapy.